In-Vitro Antioxidant Activity of Ethanolic Extract of Centaurea behen - Pushplata Chougule, Reshma Pawar, Dnyanesh Limaye, Y. M. Joshi, Vilasrao Kadam (Journal of Applied Pharmaceutical Science)
The present investigation was conducted to investigate the in-vitro activity of ethanolic extract of Roots of Centaurea behens by using DPPH radical scavenging activity, nitric oxide radical scavenging activity, hydrogen peroxide radical scavenging activity, hydroxyl radical. Result suggests that the extract possess significant antioxidant activity as compared to the standard ascorbic acid and thus further in vivo investigation is required to evaluate the medicinal significance of the extract which can be used for assessing the possible therapeutic importance of the drug.
Keywords: Antioxidants, Centaurea behen, ethanolic extract, free radicals, reducing ability.